Uji Efektivitas Vaksin Flu Burung Subtipe H5N1 pada Ayam Kampung di Legok, Tangerang, Banten - Janovie, Arria; Rusdi, Rusdi; Supiyani, Atin (Bioma, 2014)
Abstract The aim of the study was to determine the effectiveness of Avian Flu Vaccine Subtype H5N1 on native chicken. There were several inclusion criteria to selected the chicks. The criteria were just native chicken in Legok, at least 8 weeks old and never been had previous vaccine program. Total of 20 chickens were used as samples. All chicken was split in two cages, cage A contained 10 chickens were treated with vaccine and cage B contained 10 chickens as a control. Then 0.5 mL of vaccine administered intramuscularly in the chicken breast. The effectiveness of vaccination determined by measuring antibody titers before and 3 weeks after vaccination program. Measurement of antibody titers obtained by HI (Hemagglutination Inhibition) test method. Result showed that antibody titers of native chicken increased after vaccination program. There were 70% of samples that have been vaccinated could be protected against the virus. Three chickens as a control had positive titers prior to vaccination with a range of 21 - 22. Key Word : test of effectiveness, homologue killed vaccine, antibody titers.